Vznik a proměny úřadu zemského hejtmana na pozdně středověkém Hlohovsku = Genesis and transformation of the governorship (landeshauptmannsamt) in the late medieval duchy of Głogów (Glogau) - Kozák, Petr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Present research indicates that the governorship of the Duchy of Glogów originated in the 13th or at the beginning of thr 14th century. However the analysis of the sources proved itto be wrong. The governorship arose in the duchy only after the local ducal dynasty becameextinct at 1476. However, the position was continuously assigned since 1488 when the dukeJohn II was expelled out of his land and the new rulers mostly did not reside in the duchy.
Keywords: Księstwo Głogowskie - 14-15 w.; Śląsk, Dolny - historia; 14-15 w.